Voles and Lemmings (Arvicolinae) of the Palaearctic Region - Kryštufek, Boris; Shenbrot , Georgy (University of Maribor Press, 2022)
As the most species-rich group of Palaearctic rodents, voles and lemmings are frequently used in various research endeavours of fundamental and applied significance. The present work integrates achievements of the genomic era with the traditional taxonomy and provides an authoritative and up-to-date taxonomic guide to the animal group which is of great interest to experts engaged in medical zoology, epidemiology, biostratigraphy, zooarchaeology, evolutionary research, population ecology, animal systematics, biodiversity conservation, museum collection management and many more biological subdisciplines. The text is supplemented by 331 illustrations and over one thousand references. Depicted are morphological details of skull and dentition of each of the 128 species and their distributions are mapped in detail. The book will allow the user to interpret intelligently and cautiously the interrelationships among species of voles and lemmings and to follow the anticipated taxonomic change with a critical eye.